Compact farms : 15 proven plans for market farms on 5 acres or less : - Volk, Josh (Storey Publishing, 2017)
Josh Volk, the proprietor of Slow Hand Farm with 20 years experience of managing small farms in the United States presents detailed farm layouts for productivity and efficiency for small farms on 5 acres or less.